Teachers’ Pedagogical Competence in School-Based Management: A Case Study in a Public Secondary School at Pare-Pare, Indonesia - Syahruddin Syahruddin; Andi Ernawati; Muhammad Natsir Ede; Mohd. Anuar B Abdul Rahman; Ahmad Johari Sihes; Khadijah Daud (Intelektual Pustaka Media Utama, 2013)
The extent of the role of teachers’ pedagogical competence on the practice of school-based management (SBM) was explored in this study. Interviews have been conducted in order to collect the qualitative data from the participant in Pare-Pare, South Celebes, Indonesia. It was discovered that the teachers’ pedagogical competence has not been developed as it was expected. Accordingly, it was reported that teachers’ creativity was limited by the domination of the government’s interference. It is suggested that in order to improve the quality of SBM, teachers’ continuing professional development is highly required.